Pre‐conceptions of Newton’s Laws of Motion of Students in Introductory Physics - Maquiling, Joel T (Archīum Ateneo, 2010)
The Force and Motion Conceptual Evaluation (FMCE) developed by R.K. Thornton and D. R. Sokoloff was utilized to evaluate the conceptual understanding of Newton’s Laws of Motion. The test was administered to 100 freshman university students enrolled in introductory physics courses. The aim is to find out the conceptual understanding of the students prior to university level instruction. Results show that the Aristotelian notion prevails despite having taken physics in their senior year in high school. This study emphasizes the importance of training high school physics teachers and the significance of a change in the teaching techniques for university level introductory physics.